2012
DOI: 10.1097/maj.0b013e318234c132
|View full text |Cite
|
Sign up to set email alerts
|

Predisposition for Disrepair in the Aged Lung

Abstract: Introduction Idiopathic pulmonary fibrosis (IPF) is a devastating progressive lung disease with an average survival of only 3 to 5 years. The mechanisms underlying the initiation and progression of IPF are poorly understood, and treatments available have only modest effect on disease progression. Interestingly, the incidence of IPF is approximately 60 times more common in individuals aged 75 years and older, but the mechanism by which aging promotes fibrosis is unclear. The authors hypothesized that aged lungs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
126
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(138 citation statements)
references
References 47 publications
11
126
1
Order By: Relevance
“…Compared with young mice, fibroblasts isolated from aged mice show reduced Thy-1 expression, increased TGF-b receptor levels, increased expression of matrix proteins when incubated with TGF-b, and a higher resistance to apoptosis. 86,88,90 Senescent lung fibroblasts have been reported to resist apoptosis through the epigenetic mechanism of histone modification, resulting in up-regulation of the antiapoptotic gene, Bcl-2, and low expression of the proapoptotic gene, Bax. 91 Although the aged lung is more susceptible to the onset of fibrosis, few studies in the lung or other organs specifically address the capacity for resolution of established fibrosis in aged models.…”
Section: Role Of Senescence and Aging In Removing Myofibroblastsmentioning
confidence: 99%
“…Compared with young mice, fibroblasts isolated from aged mice show reduced Thy-1 expression, increased TGF-b receptor levels, increased expression of matrix proteins when incubated with TGF-b, and a higher resistance to apoptosis. 86,88,90 Senescent lung fibroblasts have been reported to resist apoptosis through the epigenetic mechanism of histone modification, resulting in up-regulation of the antiapoptotic gene, Bcl-2, and low expression of the proapoptotic gene, Bax. 91 Although the aged lung is more susceptible to the onset of fibrosis, few studies in the lung or other organs specifically address the capacity for resolution of established fibrosis in aged models.…”
Section: Role Of Senescence and Aging In Removing Myofibroblastsmentioning
confidence: 99%
“…Senescence, mitochondrial dysfunction, and insufficient autophagy in the aging lung might have implications in maladaptive responses to stress. For instance, elderly mice are more vulnerable to fibrosis after injury or stress (17,21,22) and have a lower capacity for normal repair after damage (23). In this context, our group has shown that the lung's protective mechanisms against injury, such as mesenchymal stem cell differentiation, are also impaired with age (24).…”
mentioning
confidence: 97%
“…Elements of transitional remodeling have also been demonstrated in alcoholexposed rats and mice [29,61], and in alcoholic subjects [68], in post-lung transplant recipients [69], and in aging mice [26]. However, the implications of transitional remodeling are unknown.…”
Section: Discussionmentioning
confidence: 94%
“…In the injured lung, fibronectin is deposited over denuded basement membranes where it is thought to support the migration of alveolar epithelial cells during repair [25]. The excessive deposition of fibronectin, however, has been hypothesized to promote disrepair [26]. Human studies also show increased fibronectin content within the bronchoalveolar lavage fluid of smokers [27].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation